PENGARUH INDEPENDENSI AUDITOR INSPEKTORAT TERHADAP KUALITAS AUDIT DENGAN ROLE CONFLICT SEBAGAI VARIABEL MODERASI - Rusdi, Rusdi (Valid Jurnal Ilmiah, 2018)
This study aims to empirically examine the effect on audit quality and independence of the testing role conflict as a moderating variable negatively affect direct relation to the independence of audit quality. Technique sampling usingp urposive sampling by distributing  the questionnaires. Data analysis method is used residual test to enforce moderation as a pure moderator variable. The results of this study showed that the variables significantly positively independence on audit quality and independence of the interaction between role conflict negatively affect to audit quality.